Multi-phase inverter-controlled induction machine at varied rotor parameters - Omeje, Crescent Onyebuchi; Nnadi, Damian Benneth; Oti, Stephen Ejiofor (Institute of Advanced Engineering and Science, 2022)
This paper presents a step-wise modelling of a symmetrical six-phase induction machine driven by a six-phase diode clamped multi-level inverter at a varying rotor resistance and motor inertia. The machine drive process was considered in two stages. The first stage presents the dynamic behavior of the machine when a load torque of 0 Nm and 100 Nm is applied at a varied rotor external resistance value of (0.8 and 3.2) Ω with constant motor inertia. The second stage showcased the variations in the speed, electromagnetic torque and rotor current when motor inertia is varied at (0.5 and 1.5) Kg-m2 with rotor resistance held constant. A six-phase five-level diode clamped converter phase displaced by sixty degrees with a modulation index of 0.8 was modeled to drive the poly-phase machine at a reduced %THD. All machine models were simulated in MATLAB 7.11. The simulation results showed that reduced oscillations in rotor current, motor speed and torque pulsations were achieved at a varied external rotor resistance and motor inertia.